Breakfast consumption patterns, knowledge, attitude, practice and barriers among Malaysian university students - Sivagami Jayaveloo,; Norlida Mat Daud,; Hafeedza Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Breakfast is the most important meal of the day. However, university students tend to skip breakfast due to their hectic lifestyles. Therefore, the patterns, knowledge, attitude, practice (KAP), and barriers of breakfast consumption were investigated in this study via questionnaires among 396 students of Universiti Kebangsaan Malaysia. Results showed that only 35.9% of students had breakfast between 6 to 7 days per week. Chinese students had a significantly higher (p<0.001) breakfast consumption compared with other groups. These results were consistent with the KAP scores in which Chinese students had the highest scores compared to their counterparts. However, the overall KAP scores were still at moderate levels with significant (p<0.001) positive correlations were found between knowledge and attitude (r=0.421), knowledge and practice (r=0.166), and attitude and practice (r=0.443). Malay students acknowledged the high cost of breakfast as a significant (p=0.03) barrier for breakfast consumption compared to other groups. No significant difference (p>0.05) was shown in other parameters. In conclusion, the frequency of breakfast consumption among the students was still low. The focus should be emphasized on practical strategies to address the barrier and encourage behavioral change for the students.